Biological Evaluation and X‐ray Co‐crystal Structures of Cyclohexylpyrrolidine Ligands for Trypanothione Reductase, an Enzyme from the Redox Metabolism of Trypanosoma. (6th April 2018) - De Gasparo, Raoul; Brodbeck‐Persch, Elke; Bryson, Steve; Hentzen, Nina B.; Kaiser, Marcel; Pai, Emil F.; Krauth‐Siegel, R. Luise; Diederich, François
Abstract: The tropical diseases human African trypanosomiasis, Chagas disease, and the various forms of leishmaniasis are caused by parasites of the family of trypanosomatids. These protozoa possess a unique redox metabolism based on trypanothione and trypanothione reductase (TR), making TR a promising drug target. We report the optimization of properties and potency of cyclohexylpyrrolidine inhibitors of TR by structure‐based design. The best inhibitors were freely soluble and showed competitive inhibition constants ( K i ) against Trypanosoma ( T .) brucei TR and T. cruzi TR and in vitro activities (half‐maximal inhibitory concentration, IC50 ) against these parasites in the low micromolar range, with high selectivity against human glutathione reductase. X‐ray co‐crystal structures confirmed the binding of the ligands to the hydrophobic wall of the "mepacrine binding site" with the new, solubility‐providing vectors oriented toward the surface of the large active site. Abstract : Improve and preserve : Three new ligand series based on 1‐[1‐(benzo[ b ]thien‐2‐yl)cyclohexyl]piperidine, a known trypanothione reductase (TR) inhibitor scaffold, were developed through structure‐based design to improve the water solubility and affinity of this class of compounds. Their biological activity was investigated in target‐ and cell‐based assays. Two X‐ray co‐crystal structures confirmed the predicted binding mode, with ligand anchoring at the mepacrine site of the large, solvent‐exposed active site.